2017
DOI: 10.3389/fpsyg.2017.00616
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Manipulating Items Informs on the (Limited) Construct and Criterion Validity of the Humor Styles Questionnaire

Abstract: How strongly does humor (i.e., the construct-relevant content) in the Humor Styles Questionnaire (HSQ; Martin et al., 2003) determine the responses to this measure (i.e., construct validity)? Also, how much does humor influence the relationships of the four HSQ scales, namely affiliative, self-enhancing, aggressive, and self-defeating, with personality traits and subjective well-being (i.e., criterion validity)? The present paper answers these two questions by experimentally manipulating the 32 items of the HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…As in the case of aggressive humour, it would be interesting to explore whether the effects of self‐defeating humour are work context‐dependent. Furthermore, it has been also suggested that the humour present in laughing at oneself could be associated with prosocial behaviours that are characteristic of agreeableness and extroversion . Therefore, further research is needed: first, to determine whether these discrepancies are explained by contextual factors (cultural or work‐based differences), and second, to continue exploring the construct/criterion validity of the self‐defeating humour dimension .…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of aggressive humour, it would be interesting to explore whether the effects of self‐defeating humour are work context‐dependent. Furthermore, it has been also suggested that the humour present in laughing at oneself could be associated with prosocial behaviours that are characteristic of agreeableness and extroversion . Therefore, further research is needed: first, to determine whether these discrepancies are explained by contextual factors (cultural or work‐based differences), and second, to continue exploring the construct/criterion validity of the self‐defeating humour dimension .…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the self-defeating scale does not adequately measure the self-defeating humor style and might thus lead to misleading conclusions (see also Ruch & Heintz, 2017). It seems likely that the self-defeating scale is less a measure of humor than of negative self-evaluation, potentially changing the meaning of the construct and the interpretations of existing findings on the scale.…”
Section: Discussionmentioning
confidence: 99%
“…The largest overlap (i.e., lowest discriminant validity) was found between affiliative and self-enhancing. Another approach (Ruch & Heintz, 2017) involved experimentally separating the construct-relevant content (i.e., humor) and construct-irrelevant context within the HSQ items. Correlating these manipulated versions with the original HSQ scales showed that the affiliative and self-enhancing scales were mainly determined by their construct-relevant content, while the self-defeating scale was mainly determined by the construct-irrelevant context entailed in its items (e.g., going overboard).…”
Section: Construct Validity Of the Hsqmentioning
confidence: 99%
“…This is supported by the fact that the former two typically correlate with positive outcomes and the latter correlates with variables of a more negative connotation (e.g., Martin, 2007). Unfortunately, the measurement instrument to assess these humour styles shows a lack of construct and criterion validity, in particular with respect to the self-defeating humour style which might be overcome with a revision (e.g., Ruch & Heintz, 2017).…”
Section: Humour Styles/comic Stylesmentioning
confidence: 99%